Post-Marketing Surveillance of the Safety Profile of Iodixanol in the Outpatient CT Setting: A Prospective, Multicenter, Observational Study of Patient Risk Factors, Adverse Reactions and Preventive Measures in 9953 Patients - Müller, F. H. H. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: Non-interventional study in outpatient, contrast-enhanced CTMaterials and Methods: Evaluable documentation was provided for 9953 patients from 66 radiology centers across Germany. Patient characteristics, aspects of iodixanol administration, and adverse events with an at least “possible” relationship were documented on a standardized case report form (CRF) and were evaluated up to seven days after contrast medium administration.Results: About 55.5 % of patients showed one or more risk factors (e. g. impaired renal function 4.4 %, diabetes mellitus 8.5 %, hypertension 20.6 %). One third of the sites did not implement any preventive measures. Patients with a known risk for an allergy-like reaction were more likely to receive pharmacologic preventive treatment (0.5 – 50.5 %). Oral hydration was the main preventive measure in patients with renal risk factors (< 8 %) followed by intravenous hydration (1 %). Adverse drug reactions, mainly hypersensitivity reactions, occurred in 77 patients (0.74 %), but were classified as serious in only 3 patients (0.03 %). No statistically significant correlation between risk factors, preventive measures, and adverse reactions could be found.Conclusion: The use of preventive measures for CT examinations in this outpatient setting was generally low with risk patients being pre-medicated more often, depending on their history. In the routine outpatient setting, iso-osmolar iodixanol was very well tolerated in almost 10 000 patients undergoing diagnostic CT. The rate of acute and delayed adverse reactions was low. No correlation could be found between risk factors, preventive measures and the incidence of adverse drug reactions.Key Points:• Rare use of preventive measures for outpatient CT examinations.• Low rate of acute and late adverse drug reactions to iodixanol.• No correlation between risk factors, preventive measures and adverse drug reactions.Citation Format:• Müller FHH. Post-Marketing Surveillance of the Safety Profile of Iodixanol in the Outpatient CT Setting: A Prospective, Multicenter, Observational Study of Patient Risk Factors, Adverse Reactions and Preventive Measures in 9953 Patients. Fortschr Röntgenstr 2014; 186: 1028 – 1034
Keywords: CT; contrast agents; drugs/reactions; iodixanol; post-marketing surveillance; safety profile